If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 4) + 4 = 0 Reorder the terms: 7(4 + x) + 4 = 0 (4 * 7 + x * 7) + 4 = 0 (28 + 7x) + 4 = 0 Reorder the terms: 28 + 4 + 7x = 0 Combine like terms: 28 + 4 = 32 32 + 7x = 0 Solving 32 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 7x = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 7x = 0 + -32 7x = 0 + -32 Combine like terms: 0 + -32 = -32 7x = -32 Divide each side by '7'. x = -4.571428571 Simplifying x = -4.571428571
| 3.8=3.08+0.014x | | 18x+21=20x-25 | | n+2.5= | | 3.7=3.08+0.014x | | 5x-3+6x+2+2x-7=180 | | 3x^2+3y^2z=6y+6xz | | 39+3x=37.50+3.5x | | 4x^2=7x+15 | | 3.4=3.08+0.014x | | 7x-2x+6=5x+10 | | 3x^4-2x^3-2x=0 | | 4x-8+x+54=5+5x+45-2x | | 6(x+5)-(3x-4)= | | 3(2x-5)+2=(3x-1)-2(x-4) | | 5.22-1.34x=4x-0.921 | | 8x+4=12x-9 | | 3(4z-7)+8(2z+4)=0 | | 5p+yr=r-6g | | 5y-5=y-12+7y | | (16b-6)-5(3b+3)=-3 | | 5(x-4)+3x-9x=6-(2x-5)+8x | | 0.6x+0.8660y-784.8=0 | | x*x-2=11 | | -5+3v=3v-5 | | 2x+7y=18 | | X-5=-54 | | 9s+12s+4=0 | | -13+5x=4x-7-2 | | 4x-17=4x+16 | | d=4.7+2.8(7.4) | | x*x-2=31 | | 6n+8=6n |